Exporting and Innovation: Theory and Firm-Level Evidence from the People's Republic of China - Faqin Lin; Hsiao Chink Tang (Asian Development Bank (ADB), 2013)
This paper investigates how exporting affects firm innovation. We embed innovation into a firm heterogeneity model with productivity, where in equilibrium the model shows that exporters invest more in innovation, such as research and development (R&D), than non-exporters. Using firm-level data from the People's Republic of China (PRC), we apply the Levinsohn and Petrin (2003) method of estimating firm productivity and matching econometrics to control for endogeneity. The results show, on average, in contrast to non-exporters, exporters increase their R&D intensity by more than 5%, raise their R&D expenditure by more than 33%, and are 4% more likely to engage in R&D activity. In addition, we find exporting to have a smaller impact on innovation among firms that export processed goods, specifically, those in the electronics sectors, located in coastal provinces, and foreign-owned.
hdl:11540/2098
Keywords: D21; F14; O31; 330; Exporting; innovation; firm heterogeneity; matching